Interplay Between Thiamine and p53/p21 Axes Affects Antiproliferative Action of Cisplatin in Lung Adenocarcinoma Cells by Changing Metabolism of 2-Oxoglutarate/Glutamate - Aleshin, Vasily A.; Zhou, Xiaoshan; Krishnan, Shuba; Karlsson, Anna; Bunik, Victoria I. (Frontiers in Genetics, 2021)
Thiamine (vitamin B1) is often deficient in oncopatients, particularly those undergoing chemotherapy. However, interaction between the thiamine deficiency and anticancer action of drugs has not been characterized. A major natural thiamine derivative, thiamine diphosphate (ThDP), is a coenzyme of central metabolism, also known to affect transcriptional activity of the master metabolic regulator and genome guardian p53. A direct transcriptional target of p53, p21, regulates cell cycle dynamics and DNA damage response. Our work focuses on dependence of the action of the DNA damaging anticancer drug cisplatin on metabolic regulation through p53/p21 axes and cellular thiamine status in human lung adenocarcinoma cells A549. These cells are used as a model of a hardly curable cancer, known to develop chemoresistance to platinum drugs, such as cisplatin. Compared to wild type (A549WT), a stable line with a 60% knockdown of p21 (A549p21-) is less sensitive to antiproliferative action of cisplatin. In contrast, in the thiamine-deficient medium, cisplatin impairs the viability of A549p21- cells more than that of A549WT cells. Analysis of the associated metabolic changes in the cells indicates that (i) p21 knockdown restricts the production of 2-oxoglutarate via glutamate oxidation, stimulating that within the tricarboxylic acid (TCA) cycle; (ii) cellular cisplatin sensitivity is associated with a 4-fold upregulation of glutamic-oxaloacetic transaminase (GOT2) by cisplatin; (iii) cellular cisplatin resistance is associated with a 2-fold upregulation of p53 by cisplatin. Correlation analysis of the p53 expression and enzymatic activities upon variations in cellular thiamine/ThDP levels indicates that p21 knockdown substitutes positive correlation of the p53 expression with the activity of 2-oxoglutarate dehydrogenase complex (OGDHC) for that with the activity of glutamate dehydrogenase (GDH). The knockdown also changes correlations of the levels of OGDHC, GDH and GOT2 with those of the malate and isocitrate dehydrogenases. Thus, a p53/p21-dependent change in partitioning of the glutamate conversion to 2-oxoglutarate through GOT2 or GDH, linked to NAD(P)-dependent metabolism of 2-oxoglutarate in affiliated pathways, adapts A549 cells to thiamine deficiency or cisplatin treatment. Cellular thiamine deficiency may interfere with antiproliferative action of cisplatin due to their common modulation of the p53/p21-dependent metabolic switch between the glutamate oxidation and transamination.